Text-image relationships in contemporary fairy tales - Victoria Yefymenko (LingBaW)
The article analyzes relations between the text and the image as two different semiotic modes in the framework of multimodal studies. Key theoretical approaches to this issue are outlined. Visual and verbal narratives are examined at three levels: ideational, interpersonal and textual. The ideational meaning system comprises actions, characters and circumstances. The interpersonal system covers a wide range of issues connected with interaction between the reader and the characters. The textual meaning is realized by giving prominence to certain objects in the image or the text. Logico-semantic relations of elaboration, enhancement and extension are revealed. Elaboration is characterized by clarification and exemplification, the image may be more general than the text, and vice versa. Enhancement relations include various circumstances (temporal, spatial, causal), besides, both the text and the image may enhance each other. Extension adds new, semantically unrelated information and offers alternative ways of story unfolding. The research is based on contemporary picture books (J. Scieszka, L. Anholt, F. French, R. Munsch) and illustrated fairy tales (E. Delessert, B. Ensor) and directed at revealing various types of text-image relations.